The Effect of Polymer Pin Ribs on Reinforcement of Sandwich Structures - Fojtl, Ladislav; Manas, Lukas; Rusnakova, Sona (Manufacturing Technology Journal, 2018)
This research paper deals with an influence of reinforcing polymer ribs on selected mechanical properties of sandwich structures. Reinforcing epoxy ribs are produced directly by the vacuum infusion technology when resin during its flow fills the prepared holes in the polymer core. In the experiment, two rib sizes (diameters) were tested as well as two variants of hole patterns on the core surface. The possible influence of the core material was evaluated on two core material types with different thicknesses. In addition to the observed mechanical properties observed, the types of failure and changes of the sandwich panels weight were also characterized. The obtained results show a significant increase in flexural strength and stiffness of all types and shapes of prepared reinforcing polymer ribs. Positive effect was also observed in the case of edgewise compression load capacity.
Keywords: sandwich structure; polymer rib; foam core; vacuum infusion; flexural properties; edgewise compression